2000
DOI: 10.1046/j.1365-2141.2000.02108.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of stem cell factor and granulocyte colony‐stimulating factor mobilizes the highest number of primitive haemopoietic progenitors as shown by pre‐colony‐forming unit (pre‐CFU) assay

Abstract: Summary. Fifty-two patients with poor prognosis carcinoma of the breast underwent peripheral blood stem cell (PBSC) mobilization using five different regimens. The yields of primitive haemopoietic progenitors were quantified by a recently described pre-colony-forming unit (pre-CFU) assay using limiting dilution analysis (LDA). Results of days 14 and 35 pre-CFU were also correlated with conventional CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…19,23 The donor cells detected in the bloodstream of irradiated mice are probably an indication of this disruption of BM integrity by irradiation. It also has been reported that irradiation can cause an increase in cytokines, including granulocyte-macrophage colonystimulating factor (GM-CSF), [24][25][26][27][28] which are known to be BM progenitor cell mobilization reagents. Although there was a detectable level of donor cells in the bloodstream of femur-implanted ablated mice, the level of donor cells detected in the nonimplanted femur was similar between ablated and nonablated animals.…”
Section: Discussionmentioning
confidence: 99%
“…19,23 The donor cells detected in the bloodstream of irradiated mice are probably an indication of this disruption of BM integrity by irradiation. It also has been reported that irradiation can cause an increase in cytokines, including granulocyte-macrophage colonystimulating factor (GM-CSF), [24][25][26][27][28] which are known to be BM progenitor cell mobilization reagents. Although there was a detectable level of donor cells in the bloodstream of femur-implanted ablated mice, the level of donor cells detected in the nonimplanted femur was similar between ablated and nonablated animals.…”
Section: Discussionmentioning
confidence: 99%
“…The ®nding that G-CSF and GM-CSF can induce the migration of HSCs from the bone marrow to the peripheral blood (reviewed in Gazitt, 2001), has simpli®ed the procedure for stem cell harvesting for transplantation. This shows that like the hematopoietic in vitro colony forming cells, HSCs also respond to CSFs and both types of cells are induced to migrate to the peripheral blood by G-CSF and GM-CSF (Horsfall et al, 2000;Gazitt, 2001).…”
Section: Erentiation Potential Of Hematopoietic Cellsmentioning
confidence: 93%
“…24 Mobilization in breast cancer patients using the SCF plus G-CSF combination is also successful. 25 One study of high-risk breast cancer patients resulted in successful mobilization in 63% of patients, compared with 47% of patients mobilized with G-CSF alone (Po0.05). 22 None of these earlier studies have specifically explored the possible utility of SCF with G-CSF in fludarabineexposed patients.…”
Section: Introductionmentioning
confidence: 99%